(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Forensic Medicine and Toxicology (FMT) in India is undergoing a paradigm shift, with growing recognition of the need for super-speciality training to address the rising complexity of medico-legal challenges. Advances in Forensic Toxicology, Forensic Pathology, Forensic Radiology, Molecular Diagnostics, and Toxico-genomics, alongside judicial demand for precise scientific evidence, highlight the limitations of existing postgraduate curricula. This editorial article explores the future perspectives of super-speciality courses in FMT in India, examining the need, driving factors, chal lenges, local and global opportunities. Current developments in premier institutions, including AIIMS and the National Forensic Sciences University, are paving the way for structured super-speciality training, though gaps in infrastructure, faculty expertise, and regulatory frameworks persist. International benchmarks demonstrate the potential for integrat ing advanced technologies such as artificial intelligence and digital Forensics into medico-legal practices. Initiation of super-speciality programs may further add value to the subject, strengthen its scope and recognise position of India as a global leader in Forensic field. The future of super specialty courses in Forensic Medicine in India looks promising, with several developments indicating growth and recognition of the field.